The Importance of Moral Construal: Moral versus Non-Moral Construal Elicits Faster, More Extreme, Universal Evaluations of the Same Actions - Van Bavel, Jay J.; Packer, Dominic J.; Haas, Ingrid Johnsen; Cunningham, William A. (PLOS ONE, 2012)
Over the past decade, intuitionist models of morality have challenged the view that moral reasoning is the sole or even primary means by which moral judgments are made. Rather, intuitionist models posit that certain situations automatically elicit moral intuitions, which guide moral judgments. We present three experiments showing that evaluations are also susceptible to the influence of moral versus non-moral construal. We had participants make moral evaluations (rating whether actions were morally good or bad) or non-moral evaluations (rating whether actions were pragmatically or hedonically good or bad) of a wide variety of actions. As predicted, moral evaluations were faster, more extreme, and more strongly associated with universal prescriptions—the belief that absolutely nobody or everybody should engage in an action—than non-moral (pragmatic or hedonic) evaluations of the same actions. Further, we show that people are capable of flexibly shifting from moral to non-moral evaluations on a trial-by-trial basis. Taken together, these experiments provide evidence that moral versus non-moral construal has an important influence on evaluation and suggests that effects of construal are highly flexible. We discuss the implications of these experiments for models of moral judgment and decision-making.